6-Aminopyridine-3-boronic acid functionalized magnetic nanoparticles for highly efficient enrichment of cis-diol-containing biomolecules. Issue 20 (10th May 2021) - Li, Daojin; Dong, Sihan
Abstract : Boronate affinity materials, as efficient sorbents for extraction, separation and enrichment of cis -diol-containing biomolecules, have attracted more and more attention in recent years. Abstract : Boronate affinity materials, as efficient sorbents for extraction, separation and enrichment of cis -diol-containing biomolecules, have attracted more and more attention in recent years. However, conventional boronate affinity materials require a basic binding pH (usually 8.5), which gives rise to not only inconvenience in operation but also the risk of degradation of labile compounds, and suffer from low binding affinity, which make the extraction of cis -diol-containing compounds of low concentration difficult or impossible. In order to reduce the binding pH to neutral or acidic conditions and improve binding affinity, we present a type of material, 6-aminopyridine-3-boronic acid functionalized magnetic nanoparticles, with affinity towards cis -diol-containing biomolecules. 6-Aminopyridine-3-boronic acid, exhibiting low binding pH, high affinity and excellent water solubility toward cis -diol-containing compounds, was first employed as an affinity ligand. The result indicated that the boronate affinity MNPs exhibited low binding pH (5.0) and high binding affinity toward cis -diol-containing biomolecules. Such a property enabled the selective extraction of cis -diol-containing biomolecules with low concentration under neutral or acidic conditions. This feature greatly favored the selective enrichment of cis -diol-containing biomolecules with low concentration from real samples. The feasibility for practical applications was demonstrated with the selective enrichment of cis -diol-containing biomolecules with low concentration in a human urine sample.